2019
DOI: 10.1038/s41416-019-0540-4
|View full text |Cite|
|
Sign up to set email alerts
|

Tumour-infiltrating CD8+ lymphocytes and colorectal cancer recurrence by tumour and nodal stage

Abstract: BackgroundIntratumoural T-cell infiltrate intensity cortes wrelaith clinical outcome in stage II/III colorectal cancer (CRC). We aimed to determine whether this association varies across this heterogeneous group.MethodsWe performed a pooled analysis of 1804 CRCs from the QUASAR2 and VICTOR trials. Intratumoural CD8+ and CD3+ densities were quantified by immunohistochemistry in tissue microarray (TMA) cores, and their association with clinical outcome analysed by Cox regression. We validated our results using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 34 publications
6
28
0
Order By: Relevance
“…Thus, multivariate analysis was conducted following the adjustment of these factors (i.e., mutations of BRCA1/2, POLE and TP53), and the association of low-risk subtype with higher TMB remained statistically significant. Several studies have revealed that TILs play crucial roles in the tumor-immune microenvironment, immune response and prognosis of CRC (44)(45)(46)(47). In the present study, results from the CIBERSORT algorithm showed that the low-risk CRC subtype harbored a significantly higher TIL proportion compared with the high-risk group in TCGA and independent validation cohorts.…”
Section: Discussionsupporting
confidence: 51%
“…Thus, multivariate analysis was conducted following the adjustment of these factors (i.e., mutations of BRCA1/2, POLE and TP53), and the association of low-risk subtype with higher TMB remained statistically significant. Several studies have revealed that TILs play crucial roles in the tumor-immune microenvironment, immune response and prognosis of CRC (44)(45)(46)(47). In the present study, results from the CIBERSORT algorithm showed that the low-risk CRC subtype harbored a significantly higher TIL proportion compared with the high-risk group in TCGA and independent validation cohorts.…”
Section: Discussionsupporting
confidence: 51%
“…All the more because the HGP and the immune infiltrate at the TME were found to be independent of clinical risk. Not only has increased infiltration of CD8+ cytotoxic T cells been linked to prognosis in primary CRC 44 and metastatic CRC patients 24 , 40 , 45 but Katz and colleagues have also specifically correlated increased CD8+ T cell infiltration to prolonged survival following resection of CRLM. 21 Brunner et al also found that high CD8+ infiltration was linked to favourable prognosis in patients with CRLM.…”
Section: Discussionmentioning
confidence: 99%
“…Transfer of GCSFR −/− CD4 + and CD8 + cells yielded similar effects in reducing MC38 tumor growth when injected in Rag2 −/− mice. CD8 + T cells are present in different stages of CRC, with high levels of cytotoxic T cell infiltration suggesting an anti-tumor immunity (45). Intratumoral CD8 + cell infiltration may act to suppress the micrometastasis of cancer cells into other tissues (46).…”
Section: Discussionmentioning
confidence: 99%